Analysis of the Use of Longbolt Type Connections Used as Main Connections in Folding Bridges - Haniya Fatmawati; Nindyawati Nindyawati; Fajar Tamami (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2025)
This research examines the use of folding bridges as an alternative to mitigate the impact of natural disasters that frequently occur in Indonesia. Folding bridges have been used in Japan, but they are not commonly used in Indonesia. The use of folding bridges in Japan has been designed to accommodate vehicles with a maximum load of 13.8 kN, in addition to pedestrians. The folding bridge used in Japan takes up to 5 minutes to stretch over the river. This research was conducted by determining the design of the folding bridge, starting from the dimensions used to make test objects. The analysis conducted in this study is a numerical analysis of a folding bridge with a span size of 5,000 mm, utilizing a longbolt type A490 bolt connection with a diameter of 12 mm. In the longbolt connection, a 32 mm ball bearing is also installed to provide driving force for the folding bridge when it opens and closes. The main profile used in this study is the UNP profile with dimensions 75 x 40 x 5 mm. The steel girder used is a steel border plate with a thickness of 3 mm and plate specifications that have a pattern to prevent it from slipping easily. The manufacture of folding bridge test objects focuses on the primary function for pedestrians when evacuating an area affected by natural disasters. This research focuses on the numerical analysis of static loads, providing the results of deflection values, as well as the need for bolts used as connections on the main profile. Calculations related to the bolt requirements used refer to the requirements of SNI 1729: 2020. The determination of the deflection value produced by the folding bridge, which has been designed using software, refers to the requirements of RSNI T-03-2005.